Comparison of two different methods for detecting periodontal pathogenic bacteria - Telma Blanca Lombardo Bedran; Guilherme José Pimentel Lopes de Oliveira; Luis Carlos Spolidorio; Joni Augusto Cirelli; Denise Palomari Spolidorio (Universidade Estadual de Campinas, 2017)
Aim: To perform a comparative analysis between two methods for detecting Porphyromonas gingivalis, Tannerella forsythia and Porphyromonas endodontalis in periodontal plaque samples. Methods: The study sample consisted of twenty systemically healthy patients showing generalized chronic periodontitis. The subgingival samples for microbiological analysis were collected before (baseline) and 60 days after a basic periodontal therapy from 30 non-adjacent affected sites (Probing Depth (PD): 5-7 mm, Clinical Attachment Loss (CAL) ≥ 5 mm, positive for Bleeding on Probing (BOP)). Microbiological analysis was performed by PCR and qPCR. To allow a comparative analysis between both methods, qPCR was divided in three different scores (score 2: presence of more than 100 bacteria; score 1: presence of 10-100 bacteria, and score 0: absence of bacteria), in accordance to DNA quantity, while for PCR two scores were assigned: presence or absence of bacteria. Results: qPCR demonstrated higher sensitivity in the detection of these pathogens compared with PCR when scores 1 and 2 were considered positive. However, when only score 2 was considered positive, PCR and qPCR showed better agreement. Conclusions: qPCR demonstrated higher sensitivity than conventional PCR for detection of low numbers of microorganisms and can be useful for the quantification of periodontopathogens.